Perbaikan Penjatahan Air Irigasi Cara Giliran Berdasarkan Kehilangan Waktu Tempuh Aliran Air di Saluran - Muhjidin Mawardi (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1992)
Study of time allocation in rotational irrigation system was carried out in Cikesik Irrigation Scheme, Cirebon, West Java during the dry season of 1989/1990. The study aims to estimate lime loss factor in water allocation and distribution, and to demonstrate the use of time loss factor for improvement of water allocation and distribution by rotational method. Results of the study show that during the water flowing in the canal systems, there is time toss beside hydraulics and volumetric losses. All these types of losses will significantly influence on opportunity of offtake time by each tertiary blocks, and therefore, its should be used together as considerations for allocating and distributing irrigation water. By using the improved method, equity in water distribution as the main objective of the rotational water distribution will be improved.